Gregory-Aland 424 (ÖNB Cod. Theol. Gr. 302) as Imperfect Exemplar: A Study of the Manuscript’s Relationship to Gregory-Aland 250 (BnF Coislin 224) - Peterson, Jacob W. (Novum Testamentum, 2024)
GA 424 is an important Byzantine manuscript of Acts and the Catholic Epistles, the Pauline Epistles, and Revelation featuring surrounding commentary and various apparatus bound together with numerous non-biblical texts. This article identifies GA 250 as a direct copy (Abschrift) of 424’s biblical text in both content and layout. While most of the other material was also copied, it was changed, reformatted, and edited in ways that point to a conscious effort at producing a revised edition. Beyond the evidence to support understanding GA 250 as a copy of GA 424, the ability to use GA 250 to reconstruct lost original text in GA 424 is explored, their dates are reconsidered, and desiderata are offered for further investigating the evolution between the manuscripts and their location within their family of manuscripts.